2023
DOI: 10.1021/acsmaterialslett.3c00119
|View full text |Cite
|
Sign up to set email alerts
|

A New Spinel Chloride Solid Electrolyte with High Ionic Conductivity and Stability for Na-Ion Batteries

Abstract: Halide materials are of current interest as solid electrolytes for all-solid-state sodium-ion batteries (ASIBs), due to their good balance between ionic conductivity and electrochemical stability. In this work, by using density functional theory combined with deep potential model and grand potential phase diagram analysis, we report a new spinel chloride (Na 2 Y 2/3 Cl 4 ) and systemically evaluate its potential for the solid electrolyte. The spinel Na 2 Y 2/3 Cl 4 exhibits a high ionic conductivity of 0.94 mS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We recognized that a method of obtaining ionic conductivity at room temperature by extrapolating a result at high temperature could lead to a significant error for some cases. However, since such a method has been widely employed for this type of research, we strongly believe that current approach is still reliable at least for qualitatively comparing the ionic conductivity values of considered materials.…”
Section: Methodsmentioning
confidence: 99%
“…We recognized that a method of obtaining ionic conductivity at room temperature by extrapolating a result at high temperature could lead to a significant error for some cases. However, since such a method has been widely employed for this type of research, we strongly believe that current approach is still reliable at least for qualitatively comparing the ionic conductivity values of considered materials.…”
Section: Methodsmentioning
confidence: 99%
“…The lowest energy for the E C of Na 3 YCl 6 is 1.62 eV higher than Na 0 ; therefore, Na 3 YCl 6 is supposedly very stable against Na-metal, although with such a reduced electron affinity energy that it may decompose by being reduced from the surface in contact with a reductant. Using DFT simulations, Liu et al 113 proposed a new spinel chloride sodium electrolyte, Na 2 Y 2/3 Cl 4 . This electrolyte is expected to exhibit a high ionic conductivity of 0.94 mS cm −1 at RT with a low activation energy barrier for Na + ion diffusion of 0.29 eV while possessing a semiconductor energy gap 113 from −3.85 to −0.68 eV, E 0 = 0 electrons at rest in a vacuum, E g = 3.17 eV; Fig.…”
Section: Halide Electrolytesmentioning
confidence: 99%
“…Using DFT simulations, Liu et al 113 proposed a new spinel chloride sodium electrolyte, Na 2 Y 2/3 Cl 4 . This electrolyte is expected to exhibit a high ionic conductivity of 0.94 mS cm −1 at RT with a low activation energy barrier for Na + ion diffusion of 0.29 eV while possessing a semiconductor energy gap 113 from −3.85 to −0.68 eV, E 0 = 0 electrons at rest in a vacuum, E g = 3.17 eV; Fig. 4 shows the energy concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al reported a new spinel-type chloride, Na 2 Y 2/3 Cl 4 , as a superionic sodium-ion conductor. [82] The spinel skeleton is formed by edge-sharing MCl 6 (M = Na, Y in 16d site) octahedra. Na ions partially occupy the 8a (tetrahedral), 16c (octahedral) and 48f (tetrahedral) sites.…”
Section: Halides With Spinel-type Structurementioning
confidence: 99%
“…(f) heat map of calculated mutual reaction energy between solid electrolytes and cathodes. [82] Copyright © 2023, American Chemical Society. stability towards high-voltage cathodes (Figure 12e-f).…”
Section: Halides With Spinel-type Structurementioning
confidence: 99%